Initial Orbit Determination Solution Distribution with Gooding Algorithm and Performance Enhancement - Zhengyuan Zhang; Bin Li; Zhenwei Li; Xiaohong Zhang; Jizhang Sang (Space: Science & Technology)
An initial orbit determination (IOD) solution from angles-only observations of a single short orbit arc is often required for applications such as tracklet association and fast reacquisition of a newly detected space object. Modern optical observations can collect tens or even hundreds of data points over a short arc, thus enabling a large number of IOD solutions to be determined when using an IOD algorithm of 3 lines of sight (3-LOSs), such as the Gooding algorithm. It is necessary but difficult to find an optimal solution from a solution pool, particularly in the case of too short arc (TSA). Another issue in using 3-LOSs IOD methods is the neglect of perturbation effects on the observations. That is, 3-LOSs IOD methods are developed in the 2-body frame, but the observations are perturbed. Thus, the IOD solutions may have additional errors if the observations are not corrected for perturbation effects. In this study, we investigate the distribution of the semi-major axis and eccentricity of IOD solutions in a pool and find that choosing the solution with the maximum kernel density in the distribution is a much better way to determine the final solution from the pool. We also propose a technique to correct J2 secular effects on observed angle data. We use the Gooding algorithm as the basic 3-LOSs IOD algorithm to demonstrate the effectiveness of the proposed techniques in improving the IOD accuracy in the cases of short-arc ground-based observations and space-based simulation data.